A comparative study of fungicidal compounds and plant extracts against three pathogens of Arachis hypogaea - and A.K. BHARGA, A.K. SOBTI, O.P. SHARMA (Indian Phytopathology, 2002)
Peanut (Arachis hypogaea L.) produce has been affected due to collar rot (Aspergillus niger van Tieghem), dry root rot [Rhizoctonia bataticola-Macrophomina phaseolina (Tassi) Gold] in field and aflaroot (Aspergillus flavus link ex Fries) in storage and causes losses. Thiram and bavistin were found to control these diseases effectively, but their continuous use I would lead to a serious ecological pollution. Schonbeck has indicated the antimicrobial property in certain plant extracts. With this view, some plant extracts and fungicidal compounds have been assayed in vitro against three peanut pathogens.